Development of Computer-Based Role-Playing Game Mathematics Learning Media: Spatial Geometry Material in Junior High School - Mucti, Alfian; Nurmala R (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Although the development of learning media based on RPG (Role-Playing Game) and spatial geometry materials in junior high school already exists, this research deeply integrates the typical features of RPG (such as adventure narrative, quest, inventory, leveling system, and immersive visual/audio design) to visualize and manipulate spatial geometry concepts (such as surface area, volume, and nets) which are often considered abstract by junior high school students. This study was conducted to develop and examine the validity, practicality, and effectiveness of a learning medium in the form of an RPG (Role-Playing Game) for teaching three-dimensional geometry to eighth-grade students at public junior high school 5 Tarakan. The research employed Research and Development (R&D) design, following the Four-D development model consisting of four phases: Define, Design, Develop, and Disseminate. The evaluation process of the RPG Maker product was carried out through four stages: expert validation (content, media, and instructional design experts), preliminary field testing, main field testing, and operational field testing. The analysis results showed that the developed RPG game media obtained scores of 32 for feasibility, 51 for appearance and design, and 32 for accuracy, currency, and clarity — all of which were categorized as very good. Field test results further indicated that the media met the criteria for software engineering, visual communication, and instructional design. Therefore, the RPG-based game media was declared suitable for use as a learning aid at public junior high school 5 Tarakan.